Stability of a Tick-Borne Flavivirus in Milk - Offerdahl, Danielle K.; Clancy, Niall G.; Bloom, Marshall E. (Frontiers in Bioengineering and Biotechnology, 2016)
The tick-borne flaviviruses (TBFV) occur worldwide and the tick-borne encephalitis virus members of the group (TBEV) often cause severe, debilitating neurological disease in humans. Although the primary route of infection is through the bite of an infected tick, alimentary infection through the consumption of TBEV-contaminated dairy products is also well-documented and is responsible for some disease in endemic areas. Experimental infection of goats, cattle, and sheep with TBEV shows that virus can be excreted in the milk of infected animals. Additionally, the virus remains infectious after exposure to low pH levels, similar to those found in the stomach. To evaluate survival of virus in milk, we studied the stability of the BSL-2 TBFV, Langat virus, in unpasteurized goat milk over time and after different thermal treatments. Virus was stable in milk maintained under refrigeration conditions; however, there was a marked reduction in virus titer after incubation at room temperature. High temperature, short time pasteurization protocols completely inactivated the virus. Interestingly, simulation of a typical thermal regime utilized for cheese did not completely inactivate the virus in milk. These findings stress the importance of proper milk handling and pasteurization processes in areas endemic for TBEV.